Peatland microbial community responses to plant functional group and drought are depth‐dependent. Issue 20 (9th September 2021) - Lamit, Louis J.; Romanowicz, Karl J.; Potvin, Lynette R.; Lennon, Jay T.; Tringe, Susannah G.; Chimner, Rodney A.; Kolka, Randall K.; Kane, Evan S.; Lilleskov, Erik A.
Abstract: Peatlands store one‐third of Earth's soil carbon, the stability of which is uncertain due to climate change‐driven shifts in hydrology and vegetation, and consequent impacts on microbial communities that mediate decomposition. Peatland carbon cycling varies over steep physicochemical gradients characterizing vertical peat profiles. However, it is unclear how drought‐mediated changes in plant functional groups (PFGs) and water table (WT) levels affect microbial communities at different depths. We combined a multiyear mesocosm experiment with community sequencing across a 70‐cm depth gradient, to test the hypotheses that vascular PFGs (Ericaceae vs. sedges) and WT (high vs. low) structure peatland microbial communities in depth‐dependent ways. Several key results emerged. (i) Both fungal and prokaryote (bacteria and archaea) community structure shifted with WT and PFG manipulation, but fungi were much more sensitive to PFG whereas prokaryotes were much more sensitive to WT. (ii) PFG effects were largely driven by Ericaceae, although sedge effects were evident in specific cases (e.g., methanotrophs). (iii) Treatment effects varied with depth: the influence of PFG was strongest in shallow peat (0–10, 10–20 cm), whereas WT effects were strongest at the surface and middle depths (0–10, 30–40 cm), and all treatment effects waned in the deepest peat (60–70 cm). Our results underline the depth‐dependent and taxon‐specific ways that plant communities and hydrologic variability shape peatland microbial communities, pointing to the importance of understanding how these factors integrate across soil profiles when examining peatland responses to climate change.